Incidence, management and outcome of respiratory syncytial virus infection in adult lung transplant recipients: a 9-year retrospective multicentre study. (June 2021) - Testaert, Hugo; Bouet, Margaux; Valour, Florent; Gigandon, Anne; Lafon, Marie-Edith; Philit, François; Sénéchal, Agathe; Casalegno, Jean-Sébastien; Blanchard, Elodie; Le Pavec, Jérôme; Ader, Florence
Abstract: Objectives: To analyse functional outcome parameters according to antimicrobial treatments after respiratory syncytial virus (RSV)-confirmed infection in adult lung transplant recipients. Methods: A 9-year retrospective multicentre cohort study (2011–19) included adult lung transplant recipients with RSV-confirmed infection. The first endpoint determined new allograft dysfunction (acute graft rejection and chronic lung allograft dysfunction (CLAD)) 3 months after infection. Then baseline and 3 months' postinfection forced expiratory volume in 1 second (FEV1 ) values were compared according to antimicrobial treatment. Univariate logistic regression analysis was performed. Results: RSV infection was confirmed in 77 of 424 lung transplant recipients (estimated incidence of 0.025 per patient per year; 95% confidence interval 0.018–0.036). At 3 months, 22 recipients (28.8%) developed allograft dysfunction: ten (13%) possible CLAD, six (7.9%) acute rejection and six (7.9%) CLAD. Recipients with the lowest preinfection FEV1 had a greater risk of developing pneumonia (median (interquartile range) 1.5 (1.1–1.9) vs. 2.2 (1.5–2.4) L/s, p 0.003) and a higher odds of receiving antibiotics (1.6 (1.3–2.3) vs. 2.3 (1.9–2.5) L/s, p 0.017; odds ratio 0.52, 95% confidence interval 0.27–0.99). Compared to tracheobronchitis/bronchiolitis, RSV-induced pneumonia led more frequently to hospitalization (91.7%, 22 vs. 58.0%, 29, p 0.003) and intensive care unit admission (33.3%, 8 vs. 0, p < 10 -3 ). For ribavirin-treated recipients (24.7%, 19) and azithromycin prophylaxis (50.6%, 39), 3-month FEV1 values were not different from untreated recipients. The overall mortality was 2.5% at 1 month and 5.3% at 6 months, unrelated to RSV. Conclusions: At 3 months after RSV-confirmed infection, 22 recipients (28.8%) had new allograft dysfunction. Ribavirin treatment and azithromycin prophylaxis did not prevent FEV1 decline.